1996
DOI: 10.1074/jbc.271.41.25167
|View full text |Cite
|
Sign up to set email alerts
|

The ATP Binding Cassette Transporters Pdr5 and Snq2 of Saccharomyces cerevisiae Can Mediate Transport of Steroids in Vivo

Abstract: Multiple or pleiotropic drug resistance in the yeastIn this study, we demonstrate that relief of estradiol toxicity in yeast cells expressing VEO requires functional PDR5 and SNQ2 genes, since a ⌬pdr5 ⌬snq2 double deletion leads to an increased estradiol toxicity. Furthermore, using URA3 as an estradiol-inducible reporter gene, we show that Pdr5 and Snq2, when overexpressed from high-copy plasmids, can reduce the intracellular concentration of estradiol. In contrast, a ⌬pdr5 ⌬snq2 double deletion mutant accumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
117
0
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(119 citation statements)
references
References 45 publications
0
117
0
2
Order By: Relevance
“…Subsequently, the increase in URA1 expression might be related to that of URA3. Of the remaining three genes, PHO5 encodes a secreted acid phosphatase, which is involved in nucleotide-derived phosphate hydrolysis in the periplasmic space; VHR1 encodes a transcriptional activator, required for the induction of vitamin H and biotin intermediate transporters VHT1 and BIO5, respectively (Weider et al, 2006); and PDR5 encodes the plasma membrane ABC-transporter involved in cellular detoxification (Balzi et al, 1994;Mahe et al, 1996).…”
Section: Global Transcriptome Analysismentioning
confidence: 99%
“…Subsequently, the increase in URA1 expression might be related to that of URA3. Of the remaining three genes, PHO5 encodes a secreted acid phosphatase, which is involved in nucleotide-derived phosphate hydrolysis in the periplasmic space; VHR1 encodes a transcriptional activator, required for the induction of vitamin H and biotin intermediate transporters VHT1 and BIO5, respectively (Weider et al, 2006); and PDR5 encodes the plasma membrane ABC-transporter involved in cellular detoxification (Balzi et al, 1994;Mahe et al, 1996).…”
Section: Global Transcriptome Analysismentioning
confidence: 99%
“…Interestingly, homologues of Cdr1p, e.g. Pdr5p, Snq2p in S. cerevisiae and Mdr1p in humans, have also been shown to transport steroids (Barnes et al, 1996;Mahe et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Building on previous studies, which indicated that the (TM-NBF) 2 -type Yor1p, together with the (NBF-TM) 2 -type Pdr5p and Snq2p ABC transporters, are overexpressed in the PDR1-3 mutant plasma membrane (6 -8), the PDR1-3 mutant has been used as a tool that enhances the Yor1p protein level. As another investigative tool, we constructed a set of isogenic strains, in the PDR1-3 mutant, with multiple deletions of homologous ABC genes since, in situations where two or more proteins located in the same subcellular compartment share a common substrate, a clear phenotype is only seen when all the corresponding genes are deleted, as illustrated by the work of Mahé et al (9), who showed that Pdr5p and Snq2p have an overlapping transport capacity for steroids. We deleted the yeast ABC transporter-encoding genes known or suspected to 1 The abbreviations used are: YOR1, yeast oligomycin resistance; ORF, open reading frame; ABC, ATP-binding cassette; PDR, pleiotropic drug resistance; Pma1p, H ϩ -plasma membrane ATPase; PDRE, Pdr1p/ Pdr3p response element; M-C 6 -NBD-PE, 1-myristoyl-2-[6-(NBD)aminocaproyl]phosphatidylethanolamine; NBD, 7-nitrobenz-2-oxa-1,3-diazol-4-yl; SDC, synthetic complete glucose medium; YD, rich glucose medium; YG, rich glycerol medium; MES, 2-(N-morpholino)ethanesulfonic acid; PAGE, polyacrylamide gel electrophoresis; TNP, trinitrophenyl; TNP-8-azido-ATP, 2Ј,3Ј-O-(2,4,6-trinitrophenyl)-8-azido-adenosine triphosphate; MOPS, 3-(N-morpholino)propanesulfonic acid; FCCP, carbonyl cyanide p-trifluoromethoxyphenylhydrazone; PCR, polymerase chain reaction; bp, base pair(s); kb, kilobase pair(s); TM, transmembrane; NBF, nucleotide-binding fold; CFTR, cystic fibrosis transmembrane regulator.…”
mentioning
confidence: 99%